2020
DOI: 10.15407/ujpe65.9.794
|View full text |Cite
|
Sign up to set email alerts
|

Crucial Role of Water in the Formation of Basic Properties of Living Matter

Abstract: A relation between the water properties and the behavior of aqueous solutions of albumin, the main protein component of human blood plasma, has been analyzed. The dependence of the pH index of acid-base balance in aqueous albumin solutions on the albumin concentration is experimentally studied. It is shown that the temperature dependences of pH in biological solutions are determined by the properties of water, and the concentration ones by the concentration of a protein component. It is albumin that makes the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 21 publications
(29 reference statements)
3
11
0
Order By: Relevance
“…where the quantity pH(0) = pH(eq) + 𝐴 is equal to the initial pH value of the solution, pH(eq) is the final pH value of the solution (this is the pH value for the solution that is in equilibrium with atmospheric carbon dioxide), 𝑡 is the time interval passed since the solution was prepared, and 𝜏 𝑠 is the relaxation time of the solution pH. The pH values of the solutions that were in equilibrium with atmospheric carbon dioxide, pH(eq), were determined under the following conditions: for water, the acid-base balance was equal to 7.00 at the temperature 𝑇 = 25 ∘ C and to 6.63 at 𝑇 = 50 ∘ C [1, 10,11]; for water in equilibrium with atmospheric carbon dioxide, pH = 5.63 at 𝑇 = 20 ∘ C [2, 12,13]; and, for the NaCl solution in equilibrium with atmospheric carbon dioxide, pH = 5.61 at 𝑇 = 20 ∘ C [2, 3]. In addition, the following assumptions were made: the difference between the pH of dilute aqueous NaCl solutions and the pH of water in equilibrium with atmospheric CO 2 is insignificant, and the temperature dependences of the pH of dilute NaCl solutions in equilibrium with atmospheric CO 2 are similar to that of the pH in water.…”
Section: Results Of Experimentalmentioning
confidence: 99%
“…where the quantity pH(0) = pH(eq) + 𝐴 is equal to the initial pH value of the solution, pH(eq) is the final pH value of the solution (this is the pH value for the solution that is in equilibrium with atmospheric carbon dioxide), 𝑡 is the time interval passed since the solution was prepared, and 𝜏 𝑠 is the relaxation time of the solution pH. The pH values of the solutions that were in equilibrium with atmospheric carbon dioxide, pH(eq), were determined under the following conditions: for water, the acid-base balance was equal to 7.00 at the temperature 𝑇 = 25 ∘ C and to 6.63 at 𝑇 = 50 ∘ C [1, 10,11]; for water in equilibrium with atmospheric carbon dioxide, pH = 5.63 at 𝑇 = 20 ∘ C [2, 12,13]; and, for the NaCl solution in equilibrium with atmospheric carbon dioxide, pH = 5.61 at 𝑇 = 20 ∘ C [2, 3]. In addition, the following assumptions were made: the difference between the pH of dilute aqueous NaCl solutions and the pH of water in equilibrium with atmospheric CO 2 is insignificant, and the temperature dependences of the pH of dilute NaCl solutions in equilibrium with atmospheric CO 2 are similar to that of the pH in water.…”
Section: Results Of Experimentalmentioning
confidence: 99%
“…Qualitatively, this result is consistent with the fact that the equilibrium in the water environment at a temperature of 36.6 ∘ C is established during a minimum time interval, as it should be for living organisms. In addition, two local extrema at temperatures of 35 and 42 ∘ C correspond to the minimum and maximum, respectively, ends of the temperature interval, where the living matter exists [19][20][21][22][23][24][25][26][27][28]. The shortest lifetime reflects the specific features of thermal motion in water itself, since the minimum is observed at all concentrations, and the concentration growth does not lead to its displacement.…”
Section: Results Of Experimental Measurements Of Time Dependences Of ...mentioning
confidence: 99%
“…2. Temperature dependences of the equilibrium components of pH in pure water (the upper curve)[20,21] and in water that is in equilibrium with atmospheric CO 2 (the lower curve, constructed according to formula (3))…”
mentioning
confidence: 99%
“…( 4) corresponds to the initial value of the acid-base balance in pure water at the listed temperatures. The coefficient 𝐴 decreases linearly from pH 7.0 at 25 ∘ C to pH 6.65 at 50 ∘ C [2,3].…”
Section: Time Dependences Of the Acid-base Balance Of Pure Watermentioning
confidence: 99%
“…In [2,3], the temperature dependence of the acidbase balance of pure water in the interval (25-50) ∘ C was presented. It is shown that the acid-base balance of pure water decreases linearly from pH 7.0 at 25 ∘ C to pH 6.65 at 50 ∘ C. Definitely, theoretical calculations of the acid-base balance of pure distilled water show that its pH should be equal to 7.0 at 25 ∘ C. However, in experimental measurements researchers manifest the value of the acid-base balance of pure water, which is much lower than pH 7.0 [4,5].…”
Section: Introductionmentioning
confidence: 99%